2002
DOI: 10.1002/tera.10107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sera from women with systemic lupus erythematosus or antiphospholipid syndrome and recurrent abortions on human placental explants in culture

Abstract: We conclude that sera from women with SLE may directly damage the developing placenta reducing proliferation and enhancing apoptosis. Successful treatment of the women reduces that damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
2
25
2
Order By: Relevance
“…In many cases, they are of unknown etiology and always have great emotional and social impact. 5 The results obtained corroborated the existence of antibodies harmful to the rodent conceptus in vivo or to tissues from human or rodent conceptus in vitro in the women donors' blood. 1 At other times, alloantigens located on the membranes of the blood cells are the cause of fetal insults, e.g., in hemolytic anemia with or without hydrops fetalis, dangerous levels of hemolytic unconjugated bilirubin and kernicterus are the hallmarks of Rh hemolytic disease of the newborn.…”
Section: Introductionsupporting
confidence: 56%
“…In many cases, they are of unknown etiology and always have great emotional and social impact. 5 The results obtained corroborated the existence of antibodies harmful to the rodent conceptus in vivo or to tissues from human or rodent conceptus in vitro in the women donors' blood. 1 At other times, alloantigens located on the membranes of the blood cells are the cause of fetal insults, e.g., in hemolytic anemia with or without hydrops fetalis, dangerous levels of hemolytic unconjugated bilirubin and kernicterus are the hallmarks of Rh hemolytic disease of the newborn.…”
Section: Introductionsupporting
confidence: 56%
“…In this regard, it has been shown that anti-PL antibodies can induce placental thrombosis due to their ability to displace Annexin V from the trophoblast surface, leading to subsequent prothrombinase complex formation through attachment to the exposed phosphatidylserine (20,21). Moreover, anti-PL antibodies have been indicated to be able to significantly reduce trophoblast cell invasion and proliferation (22,23) and to induce trophoblast apoptosis and necrosis (24). In addition, a number of reports have described increased rates of anti-PL antibodies among women with mild preeclampsia (25,26), severe preeclampsia (11,27) or eclampsia (28), exceeding normal levels from 10% to 20%.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, thrombophilia has been reported as related to obstetric pathology; in particular, the association with intrauterine fetal death (IUFD), a complication that ranged from 4.9 to 10.4 babies in each 1,000, and where in the 12% to 50% of cases the cause remains unknown, has been confirmed [101,102] or not confirmed [103]. Two general hypotheses have been proposed to explain how heparin and aspirin may influence the obstetric outcome: the first involves prevention of aberrant coagulation, reducing placental ischemia and the second involves direct modulation of cell biology, preventing apoptosis and maintaining trophoblast proliferation [104]. The role of heparin as an anti-inflammatory agent has been the subject of much investigation.…”
Section: The Emerging Role Of Heparin In Obstetrics Pathology and Fetmentioning
confidence: 97%